Employee Management Application with Tkinter GUI - Nugroho, Alvian; Febriyani, Nisa; Kurniawan, Heri (Journal Collabits, 2024)
Employee Management Application with Tkinter GUI is software designed to make it easier for users to manage employee data efficiently. Using the graphical user interface (GUI) provided by the Tkinter library in the Python programming language, this application allows users to add, search, edit and delete employee data entries easily. Apart from that, this application is also equipped with a feature to save and load employee data from external files in JSON format. This way, users can quickly and conveniently manage their employee information without having to bother with time-consuming administrative tasks. This application provides an effective and simple solution for managing employee data for various types of organizations and businesses.